Evaluation of the toxic influence of vitamin E (dl-alpha-tocopheryl acetate) and treatment with aqueous extracts of cinnamon or anise on lipid profile and liver functions of female wistar rats - Ibrahim, Sabah; Sabahelkhier, Murwan (International Journal of Medicine, 2017)
The toxic effects of vitamin E and its treatment with aqueous extracts of Cinnamon or anise on lipid profile and liver functions of female wistar rats were examined for six weeks during September 2016 at labs in al-Neelain University. 18 rats were divided into six groups: 1. negative control group (sunflower oil), 2. Positive control group and rest groups given (1500 mg/Kg/BW/day of Vitamin E). After two hours, the four treated groups received a low dose (2.13g/Kg) and a high dose (3.20g/Kg) 20g/Kg from Cinnamon aqueous extract (CAE) and Anise aqueous extract (AAE). At the end rats were sacrificed then serum and liver tissues were analyzed. Vitamin E toxic dose had caused a significant increase in serum Triglycerides (TG), Alanine amino transferase (ALT) levels, while it decreased the levels of High-density lipoprotein (HDL), low-density lipoprotein (LDL), total cholesterol (TC) and Aspartate amino transferase (AST). All treatments decreased TG and ALT levels. CAE low dose significantly increased TC, LDL and HDL levels. CAE high dose caused a significant decrease in AST, TC, and LDL. Both doses of AAE, caused significant increases on AST levels, and only anise low dose caused a significant decrease on TC and LDL levels. Vitamin E toxic dose caused severe fatty change in liver histology, which was near normal in both doses of CAE with a small necrosis in a low dose. Only AAE low dose normalized the liver. To conclude Vitamin E oral administration with a dose of (1500 mg/Kg) induced liver injury with an elevation in ALT and TG levels, which was significantly ameliorated by both treatments. Cinnamon was better than anise in ameliorating the toxicity. Cinnamon high dose was better than Cinnamon low dose; in contrast anise low dose was better than Anise high dose.